Advances in child development and behavior. Volume 1 - Lipsitt, Lewis P.; Spiker, Charles C. (Academic Press, 1963)
The volume contains 9 articles by 11 authors. 8 of the articles are critical reviews of research topics in child development and the 9th illustrates the application of functional analysis to abstraction learning and social reinforcement in children. The topics reviewed are responses to novel stimulation, word associations and verbal behavior, changes in stature and body weight, discrimination sets, discrimination learning among normals and retardates, learning in the first year, stimulus compounding, and the development of "overconstancy" in space perception.